2011
DOI: 10.1186/ar3305
|View full text |Cite
|
Sign up to set email alerts
|

Update on peripheral mechanisms of pain: beyond prostaglandins and cytokines

Abstract: The peripheral nociceptor is an important target of pain therapy because many pathological conditions such as inflammation excite and sensitize peripheral nociceptors. Numerous ion channels and receptors for inflammatory mediators were identified in nociceptors that are involved in neuronal excitation and sensitization, and new targets, beyond prostaglandins and cytokines, emerged for pain therapy. This review addresses mechanisms of nociception and focuses on molecules that are currently favored as new target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
98
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(103 citation statements)
references
References 49 publications
0
98
0
5
Order By: Relevance
“…The clinical consequences are hyperalgesia (greater levels of perceived pain in response to painful stimuli) and allodynia (pain in response to stimuli such as touch which normally do not evoke pain) in tissues sensitized by this process. [29] Neuropathic pain is associated with damage to the nervous system. [30,31] a long-lasting increase in the excitability and responsiveness of neurons in the CNS that results in hyperalgesia and allodynia.…”
Section: Understanding Chronic Painmentioning
confidence: 99%
“…The clinical consequences are hyperalgesia (greater levels of perceived pain in response to painful stimuli) and allodynia (pain in response to stimuli such as touch which normally do not evoke pain) in tissues sensitized by this process. [29] Neuropathic pain is associated with damage to the nervous system. [30,31] a long-lasting increase in the excitability and responsiveness of neurons in the CNS that results in hyperalgesia and allodynia.…”
Section: Understanding Chronic Painmentioning
confidence: 99%
“…By binding to G protein-coupled receptors, prostaglandin E 2 increases cAMP which subsequently activates PKA in cells. This pathway enhances excitability of neurons by sensitizing ion channels in membranes such as TRPV1 receptors and Na þ channels (Schaible et al 2011). On the other hand, the mechanical hypernociception induced by bradykinin involves an indirect activation of PKA and a direct activation of B 2 receptor-mediated phospholipase C (PLC) which in turn leads to the production of PKC resulting in the sensitization of sensory ion channels which subsequently leads to hypernociception Linley et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These mediators facilitate the electrical activity of the neuronal membrane by acting on neuronal receptors directly resulting in the activation of several molecular mechanisms which subsequently causes hypernociception (Linley et al 2010;Schaible et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown elevated intraneuronal NGF levels during inflammatory processes. These increased levels are associated with increased BDNF expression, which, although not contributing to the processing of nociceptive information in normal circumstances, contributes to inflammatory hypersensitivity 30 . It has been reported that the use of a receptor-inactivating protein (TrkA-IgG) to block the effects of endogenous NGF resulted in a reduction in sensitivity to thermal stimuli but no change in sensitivity to mechanical stimuli, showing that peripheral sensitivity can be regulated by NGFs 31 .…”
Section: Neurotrophic Factorsmentioning
confidence: 99%